Tetraphenylmethane Derivatives Containing Nitrogen Heterocycles - Kotha, Sambasivarao; Singh, Deepshikha (SynOpen, 2024)
We disclose a useful approach to novel tetrahedral building blocks containing N-heterocycles. Pyrrole was introduced on to the tetraphenylmethane (TPM) core by employing the RCM strategy, Clauson–Kaas reaction, Paal–Knorr condensation, and Ullmann coupling as key steps. In addition, various heterocyclic derivatives of TPM were prepared using nickel catalysts. We also studied the photophysical properties of the synthesized TPM derivatives containing different peripheral substituents and found that they exhibit high quantum yields.
Keywords: aryl iodide; heterocycles; aromatization; tetraphenylmethane; cross-coupling